Controlled 1.1–1.6 μm luminescence in gold-free multi-stacked InAs/InP heterostructure nanowires. (25th February 2015) - Zhang, Guoqiang; Tateno, Kouta; Birowosuto, Muhammad Danang; Notomi, Masaya; Sogawa, Tetsuomi; Gotoh, Hideki
Abstract: We report controlled 1.1–1.6 μ m luminescence in gold-free multi-stacked InAs/InP heterostructure nanowires (NWs). We realized the NWs by using an indium-particle-assisted vapor–liquid–solid synthesis approach. The growth temperature, as low as 320 °C, enables the formation of an atomically abrupt InP/InAs interface by supressing the diffusion and weakening the reservoir effect in the indium droplet. The low growth temperature also enables us to grow multi-stacked InAs/InP NWs in the axial direction without any growth on the NW side face. The high controllability of the growth technology ensures that the luminescence can be tailored by the thickness of InAs segment in InP NWs and cover the 1.3–1.5 μ m telecommunication window range. By using the nanoscale-spatial-resolution technology combing cathodoluminescence with scanning electron microscopy, we directly correlated the site of different-thickness InAs segments with its luminescence property in a single NW and demonstrate the InAs-thickness-controlled energy of optical emission in 1.1–1.6 μ m.